ANALISIS SWOT BALANCED SCORECARD (BSC) DALAM KEBIJAKAN PENGEMBANGAN UMKM BATIK DI KABUPATEN KEDIRI - Suwarno, Suwarno; Pramono, Teguh (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.07.TAHUN 2020, 2020)
The policy model strategy in empowering MSMEs in this study uses the Balanced Scorecard as an analysis method. The first stage begins with a SWOT analysis. The SWOT analysis aims to find out how the position of MSMEs is in quadrant positions one, two, three, or four. From the analysis results, it is known that the position of the UMKM batik in Kediri is currently in good condition but faces challenges that must be faced in the future so the strategy that must be carried out is a horizontal integration strategy. The second stage, after the selection of strategic recommendations using the SWOT method, will be measured based on the perspective of the Policy Model that can be implemented in the work program. The four perspectives are Customer Perspective, Financial Perspective, Learning and Growth Perspective, and Internal Business Perspective. The perspective of the policy model covers aspects of venture capital, markets, product quality, marketing, and human resources. Every indicator in the existing policy model must be implemented by applying it in the government policy program.